Simulação computacional em escala microestrutural de compósitos cerâmicos - Luchini, Bruno (Universidade Federal de São Carlos, 2017)
The study of ceramic composites assisted by computer simulation is well spread nowadays. It is an interest of the ceramic industry the development of materials models trustfully enough to reduce cost with prototypes and virtually explore an infinitude of materials compositions and thermomechanical loads. The mismatch of thermal and mechanical properties among the composite’s phases may induce decohesions or cracks after temperature variation. The computer modeling of this behavior could auxiliate the planning of the systems’ composition, as it becomes possible to evaluate the influence of the concentration of an specific constituent on the global behavior. The present dissertation aims to analyze the role of the geometrical feature, such as inclusion radius and volume fraction, in the composite behavior submitted to temperature variation. It was also analyzed the application of coesive elements to simulate the cracking phenomena in ceramic systems. The main results of this dissertation were not only the thermomechanical properties influence on the global behavior of ceramic systems, but also the construction of finite element models that might be usefull to others reseachers on the investigation of the thermomechancial behavior of distincts ceramic systems.
Computational simulation in microstructural scale of ceramic composites
Keywords: Compósitos cerâmicos; Simulação computacional; Trincas interinclusões; Elementos finitos; Raio crítico; Elementos coesivos; Ceramic composites; Computer simulation; Inter-inclusion cracking; Finite elements; Critical radius; Cohesive elements; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA